Positive clinical outcomes derived from using a proprietary mixture of selected strains during pregnancy - Di Pierro, Francesco; Parolari, Annamaria; Brundu, Benedetta; Nigro, Raffaele (Acta Biomedica Atenei Parmensis, 2017)
Background: While the use of antibiotic prophylaxis is clearly advantageous to prevent streptococcal infection, it alters the composition of the gut microbiota in mothers and infants. Enterococcus faecium L3 is one of the best studied probiotic strains and shows strong antagonistic activity against Streptococcus agalactiae due to the production of bacteriocins able to inhibit common gut and vaginal pathogens. Methods: We tested an L3-based probiotic formula (iNatal®) on 127 pregnant women attending our gynaecological unit in 2015. We compared the study subjects with 279 pregnant women enrolled in the same year and with 892 other pregnant women who attended our gynaecological unit in 2013 and 2014. Results: The findings demonstrate: (a) the safety profile of the product; (b) its ability to reduce gut disorders; (c) a 6% decrease in the incidence of streptococcal colonization; (d) an approximately 30% decline in episodes of premature rupture of membranes; (e) fewer caesarean sections during labour; and (f) a reduction in pathological umbilical cord blood pH. Conclusions: Our results demonstrate that a probiotic treatment during pregnancy could have unexpected but favourable clinical results. Further randomized, double-blind, placebo controlled studies are now needed to confirm our preliminary findings.